Nilai Kosmologi pada Tata SpasiaI Permukiman Desa Kapencar, Lereng Gunung Sindoro, Wonosobo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Abstract The Kapencar Village, as one of villages on the slope of Sumbing Mountain, has cosmological concept of spatial setting. The phenqmenological research, was done by the researcher as own instrument, explored for finding the spatial cosmological value in the Kapencar villages. Some results of the research are: 1) The Kapencar Village as the Glondong vi/age, expresed the mon-copat concept, with the Kapencar village as the centre. 2) keblat wetan as a cosmological concept. Wetan orientation as a symbol of the start of living or the very previous time of people living. Two cosmological concepts of spatial setting expresed the Kapencar Village has the grand cosmologycal concept in people lining, there is keblat papat kalimo pancer (four orientations and the centre as the fifth oerintation). Kata kunc